6.170 Problems 16901 to 17000

Table 6.339: Main lookup table sequentially arranged

#

ODE

Mathematica

Maple

16901

\[ {}x +y+1+\left (2 x +2 y-1\right ) y^{\prime } = 0 \]

16902

\[ {}y^{3}+2 \left (x^{2}-x y^{2}\right ) y^{\prime } = 0 \]

16903

\[ {}y^{\prime } = \frac {2 \left (y+2\right )^{2}}{\left (x +y-1\right )^{2}} \]

16904

\[ {}4 x^{2} {y^{\prime }}^{2}-y^{2} = x y^{3} \]

16905

\[ {}y^{\prime }+x {y^{\prime }}^{2}-y = 0 \]

16906

\[ {}y^{\prime \prime }+y = 2 \cos \left (x \right )+2 \sin \left (x \right ) \]

16907

\[ {}x y^{\prime \prime \prime } = 2 \]

16908

\[ {}y^{\prime \prime } = {y^{\prime }}^{2} \]

16909

\[ {}\left (x -1\right ) y^{\prime \prime } = 1 \]

16910

\[ {}{y^{\prime }}^{4} = 1 \]

16911

\[ {}y^{\prime \prime }+y = 0 \]

16912

\[ {}y^{\prime \prime }-3 y^{\prime }+2 y = 2 \]

16913

\[ {}y^{\prime \prime } = \left (1+{y^{\prime }}^{2}\right )^{{3}/{2}} \]

16914

\[ {}{y^{\prime }}^{2}+y y^{\prime \prime } = 1 \]

16915

\[ {}y^{\prime \prime \prime \prime } = x \]

16916

\[ {}y^{\prime \prime \prime } = x +\cos \left (x \right ) \]

16917

\[ {}y^{\prime \prime } \left (x +2\right )^{5} = 1 \]

16918

\[ {}y^{\prime \prime } = x \,{\mathrm e}^{x} \]

16919

\[ {}y^{\prime \prime } = 2 x \ln \left (x \right ) \]

16920

\[ {}x y^{\prime \prime } = y^{\prime } \]

16921

\[ {}x y^{\prime \prime }+y^{\prime } = 0 \]

16922

\[ {}x y^{\prime \prime } = \left (2 x^{2}+1\right ) y^{\prime } \]

16923

\[ {}x y^{\prime \prime } = y^{\prime }+x^{2} \]

16924

\[ {}x \ln \left (x \right ) y^{\prime \prime } = y^{\prime } \]

16925

\[ {}x y = y^{\prime } \ln \left (\frac {y^{\prime }}{x}\right ) \]

16926

\[ {}2 y^{\prime \prime } = \frac {y^{\prime }}{x}+\frac {x^{2}}{y^{\prime }} \]

16927

\[ {}y^{\prime \prime \prime } = \sqrt {1-{y^{\prime \prime }}^{2}} \]

16928

\[ {}x y^{\prime \prime \prime }-y^{\prime \prime } = 0 \]

16929

\[ {}y^{\prime \prime } = \sqrt {1+{y^{\prime }}^{2}} \]

16930

\[ {}y^{\prime \prime } = {y^{\prime }}^{2} \]

16931

\[ {}y^{\prime \prime } = \sqrt {1-{y^{\prime }}^{2}} \]

16932

\[ {}y^{\prime \prime } = 1+{y^{\prime }}^{2} \]

16933

\[ {}y^{\prime \prime } = \sqrt {1+y^{\prime }} \]

16934

\[ {}y^{\prime \prime } = y^{\prime } \ln \left (y^{\prime }\right ) \]

16935

\[ {}y^{\prime \prime }+y^{\prime }+2 = 0 \]

16936

\[ {}y^{\prime \prime } = y^{\prime } \left (1+y^{\prime }\right ) \]

16937

\[ {}3 y^{\prime \prime } = \left (1+{y^{\prime }}^{2}\right )^{{3}/{2}} \]

16938

\[ {}y^{\prime \prime \prime }+{y^{\prime \prime }}^{2} = 0 \]

16939

\[ {}y y^{\prime \prime } = {y^{\prime }}^{2} \]

16940

\[ {}y^{\prime \prime } = 2 y y^{\prime } \]

16941

\[ {}3 y^{\prime } y^{\prime \prime } = 2 y \]

16942

\[ {}2 y^{\prime \prime } = 3 y^{2} \]

16943

\[ {}{y^{\prime }}^{2}+y y^{\prime \prime } = 0 \]

16944

\[ {}y y^{\prime \prime } = y^{\prime }+{y^{\prime }}^{2} \]

16945

\[ {}y y^{\prime \prime } = 1+{y^{\prime }}^{2} \]

16946

\[ {}2 y y^{\prime \prime } = 1+{y^{\prime }}^{2} \]

16947

\[ {}y^{3} y^{\prime \prime } = -1 \]

16948

\[ {}y y^{\prime \prime }-{y^{\prime }}^{2} = y^{\prime } y^{2} \]

16949

\[ {}y^{\prime \prime } = {\mathrm e}^{2 y} \]

16950

\[ {}2 y y^{\prime \prime }-3 {y^{\prime }}^{2} = 4 y^{2} \]

16951

\[ {}y^{\prime \prime \prime } = 3 y y^{\prime } \]

16952

\[ {}y^{\prime \prime }-y = 0 \]

16953

\[ {}3 y^{\prime \prime }-2 y^{\prime }-8 y = 0 \]

16954

\[ {}y^{\prime \prime \prime }-3 y^{\prime \prime }+3 y^{\prime }-y = 0 \]

16955

\[ {}y^{\prime \prime }+2 y^{\prime }+y = 0 \]

16956

\[ {}y^{\prime \prime }-4 y^{\prime }+3 y = 0 \]

16957

\[ {}y^{\prime \prime \prime }+6 y^{\prime \prime }+11 y^{\prime }+6 y = 0 \]

16958

\[ {}y^{\prime \prime }-2 y^{\prime }-2 y = 0 \]

16959

\[ {}y^{\left (6\right )}+2 y^{\left (5\right )}+y^{\prime \prime \prime \prime } = 0 \]

16960

\[ {}4 y^{\prime \prime }-8 y^{\prime }+5 y = 0 \]

16961

\[ {}y^{\prime \prime \prime }-8 y = 0 \]

16962

\[ {}y^{\prime \prime \prime \prime }+4 y^{\prime \prime \prime }+10 y^{\prime \prime }+12 y^{\prime }+5 y = 0 \]

16963

\[ {}y^{\prime \prime }-2 y^{\prime }+2 y = 0 \]

16964

\[ {}y^{\prime \prime }-2 y^{\prime }+3 y = 0 \]

16965

\[ {}y^{\prime \prime \prime \prime }+2 y^{\prime \prime \prime }+4 y^{\prime \prime }-2 y^{\prime }-5 y = 0 \]

16966

\[ {}y^{\left (5\right )}+4 y^{\prime \prime \prime \prime }+5 y^{\prime \prime \prime }-6 y^{\prime }-4 y = 0 \]

16967

\[ {}y^{\prime \prime \prime }+2 y^{\prime \prime }-y^{\prime }-2 y = 0 \]

16968

\[ {}y^{\prime \prime \prime }-2 y^{\prime \prime }+2 y^{\prime } = 0 \]

16969

\[ {}y^{\prime \prime \prime \prime }-y = 0 \]

16970

\[ {}y^{\left (5\right )} = 0 \]

16971

\[ {}y^{\prime \prime \prime }-3 y^{\prime }-2 y = 0 \]

16972

\[ {}2 y^{\prime \prime \prime }-3 y^{\prime \prime }+y^{\prime } = 0 \]

16973

\[ {}y^{\prime \prime \prime }+y^{\prime \prime } = 0 \]

16974

\[ {}y^{\prime \prime }+3 y^{\prime } = 3 \]

16975

\[ {}y^{\prime \prime }-7 y^{\prime } = \left (x -1\right )^{2} \]

16976

\[ {}y^{\prime \prime }+3 y^{\prime } = {\mathrm e}^{x} \]

16977

\[ {}y^{\prime \prime }+7 y^{\prime } = {\mathrm e}^{-7 x} \]

16978

\[ {}y^{\prime \prime }-8 y^{\prime }+16 y = \left (1-x \right ) {\mathrm e}^{4 x} \]

16979

\[ {}y^{\prime \prime }-10 y^{\prime }+25 y = {\mathrm e}^{5 x} \]

16980

\[ {}4 y^{\prime \prime }-3 y^{\prime } = x \,{\mathrm e}^{\frac {3 x}{4}} \]

16981

\[ {}y^{\prime \prime }-4 y^{\prime } = x \,{\mathrm e}^{4 x} \]

16982

\[ {}y^{\prime \prime }+25 y = \cos \left (5 x \right ) \]

16983

\[ {}y^{\prime \prime }+y = \sin \left (x \right )-\cos \left (x \right ) \]

16984

\[ {}y^{\prime \prime }+16 y = \sin \left (4 x +\alpha \right ) \]

16985

\[ {}y^{\prime \prime }+4 y^{\prime }+8 y = {\mathrm e}^{2 x} \left (\sin \left (2 x \right )+\cos \left (2 x \right )\right ) \]

16986

\[ {}y^{\prime \prime }-4 y^{\prime }+8 y = {\mathrm e}^{2 x} \left (\sin \left (2 x \right )-\cos \left (2 x \right )\right ) \]

16987

\[ {}y^{\prime \prime }+6 y^{\prime }+13 y = {\mathrm e}^{-3 x} \cos \left (2 x \right ) \]

16988

\[ {}y^{\prime \prime }+k^{2} y = k \sin \left (k x +\alpha \right ) \]

16989

\[ {}y^{\prime \prime }+k^{2} y = k \]

16990

\[ {}y^{\prime \prime \prime }+y = x \]

16991

\[ {}y^{\prime \prime \prime }+6 y^{\prime \prime }+11 y^{\prime }+6 y = 1 \]

16992

\[ {}y^{\prime \prime \prime }+y^{\prime } = 2 \]

16993

\[ {}y^{\prime \prime \prime }+y^{\prime \prime } = 3 \]

16994

\[ {}y^{\prime \prime \prime \prime }-y = 1 \]

16995

\[ {}y^{\prime \prime \prime \prime }-y^{\prime } = 2 \]

16996

\[ {}y^{\prime \prime \prime \prime }-y^{\prime \prime } = 3 \]

16997

\[ {}y^{\prime \prime \prime \prime }-y^{\prime \prime \prime } = 4 \]

16998

\[ {}y^{\prime \prime \prime \prime }+4 y^{\prime \prime \prime }+4 y^{\prime \prime } = 1 \]

16999

\[ {}y^{\prime \prime \prime \prime }+2 y^{\prime \prime \prime }+y^{\prime \prime } = {\mathrm e}^{4 x} \]

17000

\[ {}y^{\prime \prime \prime \prime }+2 y^{\prime \prime \prime }+y^{\prime \prime } = {\mathrm e}^{-x} \]